Six new species of Afrotropical Allodia (Diptera: Mycetophilidae): DNA barcodes indicate recent diversification with a single origin - Magnussen, Trude; Kjærandsen, Jostein; Johnsen, Arild; Søli, Geir E. E. (Zootaxa, 2018)
Only one species of the genus Allodia has been previously recorded from the Afrotropical region, Allodia (Brachycampta) flavorufa Matile, 1978. Six new species are described here, all representing the nominotypical subgenus, Allodia s.s. The new species are described from material collected in different mountainous areas in south and east Africa; A. jaschhofi sp. nov., A. karkloofensis sp. nov., A. drakensbergensis sp. nov., A. nyeriensis sp. nov., A. mazumbaiensis sp. nov. and A. keurbosensis sp. nov. The species are morphologically very similar, and can only be separated based on minor differences in wing venation and characters of the male terminalia. The genetic differences between the species in the DNA barcode region (CO1), however, support delimitation. The origin and distribution of these Afrotropical taxa, in relation to each other and to their Holarctic relatives, is discussed.